2009
DOI: 10.3126/jnbs.v5i1.2084
|View full text |Cite
|
Sign up to set email alerts
|

Credit for the Poor: The Experience of Rural Development Scheme of Islami Bank Bangladesh Ltd.

Abstract: Islami

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Khan (2010) and Ullah (2011) found from their empirical investigation in Pakistan that if the loan is provided to the 40 or more age's clients this will increase their income and social welfare. On the other hand, Uddin, (2008) argued that comparatively, young age person is better to put dedication, willingness, and importance to be success in business…”
Section: Age Of Borrowersmentioning
confidence: 99%
See 2 more Smart Citations
“…Khan (2010) and Ullah (2011) found from their empirical investigation in Pakistan that if the loan is provided to the 40 or more age's clients this will increase their income and social welfare. On the other hand, Uddin, (2008) argued that comparatively, young age person is better to put dedication, willingness, and importance to be success in business…”
Section: Age Of Borrowersmentioning
confidence: 99%
“…Bhuiyian et. All (2013), Uddin (2008), Ahmad (2002, also studied the impact on same countries and same IMFIs. The authors found that RDS microfinance borrowers are using the loan to increase their income.…”
Section: Impact On Income and Consumption Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…[15], [16] and [17] also studied the impact on same countries and same IMFIs. The authors found that RDS microfinance borrowers have a better record of using the loan for income generating activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the literature showed that microfinance borrowers' income and expenditure are affected by some factors. Many researchers such as [13], [14], [17], [18] [23], [24], used many factors such as amount of loan, training etc. Thus, this study considered these factors as the independent variables.…”
Section: Literature Reviewmentioning
confidence: 99%